Brachystelma ananthagiriense (Apocynaceae), a new species from Ananthagiri hills, Telangana, India. (16th July 2021) - Paramesh, L.; Prasad, K.; Sadasivaiah, B.; Vijaya Bhasker Reddy, A.
Abstract : A new species of Brachystelma, B. ananthagiriense is described and illustrated from the Ananthagiri hills of Vikarabad district, Telangana. The new species is closely similar to B. gondwanense but differs in a few attributes which are discussed. A detailed description, photographs and the conservation status of the new species are provided.